(untitled) (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2025)
Vocabulary mastery is a fundamental aspect of learning English because it plays an important role in the four language skills: listening, speaking, reading, and writing. However, many students struggle to master vocabulary due to low motivation, monotonous learning methods, and minimal use of interactive media. This study aims to improve the English vocabulary mastery of grade VII students of SMP Negeri 3 Penebel through Wordwall-based learning media in the Contextual Teaching and Learning (CTL) approach. The method used is pre-experimental with a one-group pretest-posttest design. Data were collected through tests, observations, and questionnaires and then analyzed quantitatively and qualitatively. The expected results are a significant increase in students’ vocabulary mastery after applying Wordwall media and increased student interest and participation in the learning process.